Non-Adherence to Anti-Tuberculosis Treatment amongst Patients in Montserrado County, Liberia - Corvah, A.B. (University of Ghana, 2021)
Background Non- adherence to tuberculosis treatment which serves as one of the most substantial hindrances to TB control is an important barrier and is now influencing TB treatment failure, relapse and death. However, Liberia is amongst countries in the world where national prevalence of TB and non-adherence rate is unknown. Therefore, this study aimed to assess factors related with non-adherence to anti-TB treatment amongst patients in Montserrado County, Liberia Methods A facility based cross sectional study was conducted in four (4) health facilities in Montserrado County, 2019. We collected data using semi-structured questionnaire. We useda random number table which is the number between 1 and 7 was selected as a starting point. A skip interval of 6 was used. The Morisky Medical Adherence 8 item scale (MMAS-8) was used to assessed patients’ non-adherence level. MMAS-8 is a self-reported assessment tool used to and measure medication-taking behavior. We defined non-adherence as an individual scoring < 6 points in the MMAS-8. Changes between variables were assessed using the chi- square test and Fisher’s exact tests. Multiple logistic regression analysis was conducted on allfactors used to declare the independently associated predictors that were statistically significant at a confidence interval of 95% and P value < 0.05 Results A total of 317 TB patients participated in the study. Majority of participants were males and age group 30 to 39years accounted for 90 (28.4%). The overall non-adherence to anti-tuberculosis treatment was 25.9% (95%CI = 21.3 – 31.0%). Almost Half 49 (59.8%) of the non-adherents indicated they had ever missed their appointment. Nonadherence was found to be significantly associated with pill burden (cOR 4.00, 95%CI: 2.10 - 7.65), Changes in family/friends relationship (aOR 8.30, 95%CI: 2.40 - 28.73), longest period of time one failed to take TB medication (cOR 2.48, 95%CI: 1.02 - 6.07), and availability of food intake (aOR 82 ,95%CI:0.32 - 10.29) and patient ease of strictly following medication (aOR 0.051, 95%CI: 0.01 - 0.27) Conclusion Our findings proposed that non-adherence was high among TB patients. Non-adherence was higher in male respondents found within the age group 30-39 years. Patients who consumed at least 3-4 pills daily under the direct observation of treatment supporters were less likely to adhere to treatment plan. Family members’ poor relationship with patients, lack of transportation and unavailability of drugs contributed to patients’ non-adherence. Therefore, we recommended strengthening the health providers to provide constant health education to patients and their families, decentralize TB services and ensure regular supply of drugs for improved adherence.
MA. Public Health
Keywords: Tuberculosis; Liberia; Montserrado County